Welcome to America! Mad Men, Media, Masculinities, and the American Imaginary (Intercom - Brazilian Journal of Communication Sciences, 2024)
This paper aims to analyze how the narrative of Mad Men is committed to the imagery of Americanism, grounded in the myth of the self-made man and the American way of life. The object of study was the Mad Men TV series, interpreted through the myth criticism of Gilbert Durand in dialogue with the theoretical assumptions of Edgar Morin. The resultsindicate a feedback loop of conservative imagery in pursuit of a golden age marked by misogyny, male dominance, and mass consumption.